How to Find Information Online - StJohn, Amanda; Ostrom, Bob (New York : AV2 by Weigl, 2018)
When Opal Owl and Stew Rabbit find a turtle, they go to the public library to learn the difference between a turtle and a tortoise. The librarian helps them with an online search. Opal and Stew learn the difference between a fact and an opinion, and how to check online sources.
Keywords: Online library catalogs -- Juvenile literature; Internet searching -- Juvenile literature; Public libraries -- Juvenile literature; Children's libraries -- Juvenile literature